2013
DOI: 10.1088/0957-4484/24/20/205402
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous increase in electrical conductivity and Seebeck coefficient in highly boron-doped nanocrystalline Si

Abstract: A large thermoelectric power factor in heavily boron-doped p-type nanograined Si with grain sizes ∼30 nm and grain boundary regions of ∼2 nm is reported. The reported power factor is ∼5 times higher than in bulk Si. It originates from the surprising observation that for a specific range of carrier concentrations, the electrical conductivity and Seebeck coefficient increase simultaneously. The two essential ingredients for this observation are nanocrystallinity and extremely high boron doping levels. This exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 46 publications
10
135
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13] Due to this drastic reduction in j, which is quickly reaching the amorphous limit, further improvements might come from the thermoelectric power factor (PF ¼ S 2 r), for which to date limited progress has been made. However, a small set of recent studies have demonstrated that a significant improvement in the PF of Si is sometimes possible for polycrystalline Si [14][15][16] where built-in potential barriers are created by nanoscale grain boundaries or voids, 17 combined with high levels of doping. These potential barriers increase energy filtering and as a consequence, the Si Seebeck coefficient.…”
Section: à3mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12][13] Due to this drastic reduction in j, which is quickly reaching the amorphous limit, further improvements might come from the thermoelectric power factor (PF ¼ S 2 r), for which to date limited progress has been made. However, a small set of recent studies have demonstrated that a significant improvement in the PF of Si is sometimes possible for polycrystalline Si [14][15][16] where built-in potential barriers are created by nanoscale grain boundaries or voids, 17 combined with high levels of doping. These potential barriers increase energy filtering and as a consequence, the Si Seebeck coefficient.…”
Section: à3mentioning
confidence: 99%
“…This is because the overall Seebeck coefficient is determined by the weighted average of S in the two regions, with the weighting factor being the temperature drop in each region, determined by their thermal conductivities. 14,22 Thus, as the crystal lattice is healed, especially in the last annealing step, and local thermal conductivity increases, the local Seebeck coefficient in the dislocation regions (which is expected to be high compared to bulk Si) becomes more important and could warrant the large increase in the overall S observed in Fig. 6(a).…”
Section: à2mentioning
confidence: 99%
“…We describe how a carefully designed Si nanograin geometry, with a carefully designed underlying potential distribution and dopant distribution, can make effective use of energy filtering and structure inhomogeneities, and provide large TE power factors, even up to ~5× higher compared to bulk Si. We present simple explanations for this behavior, backed by recent experimental observations [26,27]. We then discuss the prospect of Si nanomeshes (or nanoporous Si)…”
Section: Dos(e)mentioning
confidence: 77%
“…In our recent works, however, we showed that very large power factors can be achieved in nanocrystalline bulk-like Si materials [26,27,54].…”
Section: Thermoelectric Properties Of Bulk-size Nanostructured Simentioning
confidence: 93%
“…The work of Ref. [12,16] has demonstrated very high power factors in Si-based nanocomposites, however energy filtering was only partially responsible for this. Surprisingly, despite the fact that the energy filtering idea was suggested in the 1998 [5], still there is no theoretical investigation as to why power factor benefits are hard to realize experimentally.…”
Section: Introductionmentioning
confidence: 99%